On-Pump and Off-Pump Coronary Artery Bypass Grafting As An Open Heart Surgery Procedure In Management Of Coronary Heart Disease - Sebayang, Abed Nego Okthara; Abdulgani, Hafil Budianto (Talenta Publisher, 2023)
Introduction: Coronary heart disease is a condition in which fatty deposits in the heart's coronary arteries change the role and shape of the streets and obstruct blood flow to the heart. Invasive management is known as coronary artery bypass grafting and is divided into two techniques: on-pump coronary artery bypass and off-pump coronary artery bypass. Method: The method used in this study is a systematic review. The literature study conducted by the author is by searching various written sources, whether in the form of books, archives, magazines, articles and journals, or documents that are relevant to the problem being studied. Discussion: The on-pump coronary artery bypass technique is performed using a cardiopulmonary bypass machine which replaces the function of the heart and lungs during the operation process, and the off-pump coronary artery bypass technique is performed without using a cardiopulmonary bypass machine so that the heart keeps beating during the operation. Both of these techniques give equally good results, and their selection depends on the clinical situation of the patient and the cardiac surgeon. Conclusion: Coronary artery bypass grafting is a surgical technique that is currently the choice in managing coronary heart disease patients when treatment and Percutaneous coronary intervention do not provide the best results. There are two techniques for performing CABG, namely on-pump coronary artery bypass and off-pump coronary artery bypass Keyword: Coronary heart disease,Â Coronary Artery, On pump coronary artery bypass, off-pump coronary artery bypass Â Pendahuluan: Penyakit jantung koroner adalah suatu kondisi di mana timbunan lemak di arteri koroner jantung mengubah peran dan bentuk jalan dan menghalangi aliran darah ke jantung. Penatalaksanaan invasif dikenal sebagai pencangkokan bypass arteri koroner dan dibagi menjadi dua teknik: bypass arteri koroner on-pump dan bypass arteri koroner off-pump. Metode: Metode yang digunakan dalam penelitian ini adalah sistematika review. Studi kepustakaan yang dilakukan penulis adalah dengan menelusuri berbagai sumber tertulis, baik berupa buku, arsip, majalah, artikel dan jurnal, maupun dokumen-dokumen yang relevan dengan masalah yang diteliti. Diskusi: Teknik bypass arteri koroner on-pump dilakukan dengan menggunakan mesin cardiopulmonary bypass yang menggantikan fungsi jantung dan paru-paru selama proses operasi, dan teknik bypass arteri koroner off-pump dilakukan tanpa menggunakan mesin cardiopulmonary bypass sehingga jantung terus berdetak selama operasi. Kedua teknik ini memberikan hasil yang sama baiknya, dan pemilihannya tergantung pada situasi klinis pasien dan ahli bedah jantung. Kesimpulan: Pencangkokan bypass arteri koroner merupakan teknik bedah yang saat ini menjadi pilihan dalam penanganan pasien penyakit jantung koroner ketika pengobatan dan intervensi koroner perkutan tidak memberikan hasil terbaik. Ada dua teknik untuk melakukan CABG, yaitu bypass arteri koroner on-pump dan bypass arteri koroner off-pump Kata Kunci:Â penyakit jantung koroner, arteri koroner, bedah pintas koroner